1995
DOI: 10.1063/1.468980
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectroscopy and photodissociation dynamics of small helium cluster ions

Abstract: The optical absorption of size-selected helium cluster ions was studied via photofragmentation spectroscopy. Absorption cross sections were measured for He n ϩ ͑nϭ3, 4, 10, 21, and 30͒. A broad absorption peak was found, which for He 3 ϩ is centered at Ϸ5.3 eV, and which with increasing cluster size shifts slightly to the red. In addition, the kinetic energy release to the ionized and neutral photofragments was measured by a time-of-flight technique for cluster sizes between nϭ3 and 10. From the energy balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 21 publications
5
46
1
Order By: Relevance
“…Thus, it can create a fast ionic and a fast neutral fragment, together with a slow neutral signal from the central helium atom as the system breaks up symmetrically along such a reaction coordinate, as seen in the experiments. 8 It therefore becomes of interest to further find out if other nuclear regions of the relevant PES still support this explanation and what is the possible role played by bent structures of the trimer ions in case they happen to be formed during the ionic cluster preparation after supersonic expansion.…”
Section: A the Linear Configurationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it can create a fast ionic and a fast neutral fragment, together with a slow neutral signal from the central helium atom as the system breaks up symmetrically along such a reaction coordinate, as seen in the experiments. 8 It therefore becomes of interest to further find out if other nuclear regions of the relevant PES still support this explanation and what is the possible role played by bent structures of the trimer ions in case they happen to be formed during the ionic cluster preparation after supersonic expansion.…”
Section: A the Linear Configurationsmentioning
confidence: 99%
“…Another, interesting experimental result showed that the product time-of-flight spectra of He 3 ϩ contain peaks related to one fast neutral He atom, to one fast ionic He ϩ and to a third slow neutral He atom. 8 This pattern was explained by our calculations when we examined the linear symmetric dissociative path, 9 and where we showed that the relevant excited electronic state, which can be reached via a dipoleallowed transition (1 2 ⌺ u ϩ ←X 2 ⌺ g ϩ ) yields a modified electronic density distribution where the positive charge now resides on one of the two wing He atoms, even for cluster geometries still within the Frank-Condon ͑FC͒ region of the Franck-Condon ground electronic configuration. Thus, it can create a fast ionic and a fast neutral fragment, together with a slow neutral signal from the central helium atom as the system breaks up symmetrically along such a reaction coordinate, as seen in the experiments.…”
Section: A the Linear Configurationsmentioning
confidence: 99%
See 3 more Smart Citations